Perlindungan Hukum terhadap Anak yang Menjadi Korban Tindak Pidana Persetubuhan di Bawah Umur - Agustinus Yitsak Mannuel Kapitan; I Made Sepud; I Nyoman Sujana (Jurnal Preferensi Hukum, 2020)
Legal protection is a legal effort that must be provided by law enforcement officials to provide a sense of security to the community both body and soul from interference and threats from any party. The protection of children who are victims of moral crimes is regulated in Law Number 23 of 2002 jo and Law Number 35 of 2014 concerning Child Protection. This research was conducted with the aim of describing the legal protection of a child who is the victim of criminal acts of sexual intercourse and the criminal sanctions against the perpetrators of the sexual intercourse crime on a child. This research was conducted using the normative legal research method. Based on the results of the research and discussion, the legal protection for children who are victims of criminal acts of intercourse is regulated in Law No. 35/2014. Children who are victims are given protection in the form of medical assistance, psycho-rehabilitation, the right to restitution, the right to compensation. Criminal sanctions against the perpetrator of the criminal act of child sexual intercourse in decision number 58 / Pid.Sus / 2015 / PN.Tab, the perpetrator was sentenced to 7 (seven) years in prison and a fine of 150,000,000.00. Seeing the perpetrator's actions were very cruel, robbing other people's honor, namely his own daughter, the punishment that should be given to the perpetrator is the maximum punishment. If the fine cannot be paid, the defendant's sentence will be increased to 6 (six) months.